Reliability Of Risk Assessment In Petrochemical Industries - Rachid, Ouache; Ali, A. J. Adham (Penerbit Universiti Malaysia Pahang, 2015)
Quantitative Risk Assessment is one of the approaches to assess risks. A fuzzy set is a new mathematical tool to model inaccuracy and uncertainty. In this research paper, an integrate model has proposed to solve problem of uncertainty of initiative events and their consequences. Hazard and operability study, Bow-tie analysis, and layer of protection analysis are methods proposed together as the first step in the model for risk analysis. Reliability-fuzzy is the second step to deal with uncertainty, and simulation is the third step for more accurate of results. From the results realized we can judge that the integration between classical methods, fuzzy approach and simulation is greatest model for more reliability of quantitative risk assessment.